Small Farm Food Safety, Fresh Produce, Part 4: Farm Map Activity - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS, 2007)
FCS8845, a 3-page fact sheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, provides a schematic map of a theoretical farm and invites readers to identify and comment on the potential food safety risks depicted. Published by the UF Department of Family, Youth and Community Sciences, October 2007.